The Presupposition in the Dialogue of Barbie (2023): A Pragmatic Analysis on Yule’s Theory - Sagala, Dela Kristina; Handayani, Reli; Heryanti, Reny (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to identify and analyze the types of presupposition used in the film Barbie (2023), directed by Greta Gerwig. Drawing on Yule’s (1996) typology—existential, factive, lexical, non-factive, structural, and counterfactual—this research applies a descriptive qualitative method supported by a pragmatic discourse analysis approach. The data consists of selected utterances from the film’s official script, verified through repeated viewing. A total of 67 presuppositional expressions were found, with 27 data points analyzed in depth. Results reveal existential presupposition as the most dominant, typically triggered by definite noun phrases and possessive constructions. These findings demonstrate how presupposition shapes implicit meaning, enhances character development, and subtly conveys sociocultural messages in audiovisual narratives. The study contributes to pragmatic research on film discourse by uncovering how language structures perception and interaction in fictional contexts.